2006
DOI: 10.1016/j.gca.2006.06.888
|View full text |Cite
|
Sign up to set email alerts
|

Antimony quartz and antimony-gold quartz veins from northern Portugal

Abstract: In northern Portugal, there are two main areas containing antimony, lead-antimony and antimony-gold deposits. The antimony and lead-antimony quartz breccia veins from the Bragança district are mainly hosted by Silurian phyllites. The antimonygold quartz breccia veins from the Dú rico-Beirã region are mainly hosted by the Cambrian schist-metagraywacke complex and also Ordovician phyllites and quartzites. These veins are up to 200 m long, but their thickness ranges from a few centimeters to 3.6 m.In each deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…4d) suggests that Sb substitutes for As as found by Cathelineau et al (1988), Couto et al (1990) and Neiva et al (2008). Both As and Sb likely replace S in pyrite as the inverse correlations of As vs. S and Sb vs. S occur (Fig.…”
Section: Mineralogical Datasupporting
confidence: 56%
See 2 more Smart Citations
“…4d) suggests that Sb substitutes for As as found by Cathelineau et al (1988), Couto et al (1990) and Neiva et al (2008). Both As and Sb likely replace S in pyrite as the inverse correlations of As vs. S and Sb vs. S occur (Fig.…”
Section: Mineralogical Datasupporting
confidence: 56%
“…However, the first stage is smaller at the Terramonte Pb-Zn-Ag quartz vein, whereas at the Ribeiro da Igreja Sb-Au deposit carbonates occur in the third stage and there is a fourth Sb-stage, indicating that their late hydrothermal fluids are richer in Sb than those from Terramonte. The Pb isotopic compositions of stibnite from the Sb-Au deposits suggest a homogeneous crustal source of lead from the metasedimentary sequences (Neiva et al, 2008).…”
Section: Mineralizing Environment and Mineral Depositionmentioning
confidence: 94%
See 1 more Smart Citation
“…Native arsenic has also been discovered in brecciated marbles in Carinthia, Austria, where the mineralization predominantly consists of native arsenic and realgar, but no gold mineralization is present (G d and Zamann, 2000). Native antimony commonly occurs in antimony deposits and Sb-enriched gold deposits (Normand et al, 1996;Kontak et al, 1996;Bellot et al, 2003;Neiva et al, 2008). Compared to native arsenic and antimony, native bismuth is more commonly seen in various gold or non-gold deposits (Skirrow and Walshe, 2002;T rm nen and Koski, 2005;Oberthur and Weiser, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, gold mineralization is more commonly associated with stibnite rather than native antimony in antimony-gold deposits (Kontak et al, 1996;Neiva et al, 2008), and with As-rich pyrite or arsenopyrite rather than native arsenic in As-rich gold deposits (Cline, 2001;Tomkins et al, 2004). The photomicrographs provided by Tomkins et al (2004) demonstrated that native arsenic was later than native gold in paragenesis.…”
Section: Introductionmentioning
confidence: 99%